Changes in Biomass and Diversity of Soil Macrofauna along a Climatic Gradient in European Boreal Forests - Kozlov Mikhail V.; Zverev Vitali; Gusarov Vladimir I.; Korobushkin Danii I.; Krivosheina Nina P.; Mattila Jaakko; Mutanen Marko; Popova Anna; Prosvirov Alexander S.; Punttila Pekka; Söderman Guy; Stańska Marzena; et al. (MDPI AG, 2022)
Latitudinal gradients allow insights into the factors that shape ecosystem structure and delimit ecosystem processes, particularly climate. We asked whether the biomass and diversity of soil macrofauna in boreal forests change systematically along a latitudinal gradient spanning from 60° N to 69° N. Invertebrates (3697 individuals) were extracted from 400 soil samples (20 × 20 cm, 30 cm depth) collected at ten sites in 2015–2016 and then weighed and identified. We discovered 265 species living in soil and on the soil surface; their average density was 0.486 g d·w·m−2. The species-level diversity decreased from low to high latitudes. The biomass of soil macrofauna showed no latitudinal changes in early summer but decreased towards the north in late summer. This variation among study sites was associated with the decrease in mean annual temperature by ca 5 °C and with variation in fine root biomass. The biomass of herbivores and fungivores decreased towards the north, whereas the biomass of detritivores and predators showed no significant latitudinal changes. This variation in latitudinal biomass patterns among the soil macrofauna feeding guilds suggests that these guilds may respond differently to climate change, with poorly understood consequences for ecosystem structure and functions.